Heat rises [compact disc, unabridged] - Castle, Richard (Hyperion Press, 2011)
During the coldest winter in recent memory, Nikki Heat is sent to the scene of an unusual murder. Her subsequent investigation uncovers an unnerving conspiracy involving the NYPD elite, and when she gets too close to the truth, Nikki is kicked off the force. With nowhere left to turn and targeted by killers, Nikki calls on the help of reporter Jameson Rook.